2020
DOI: 10.1097/md.0000000000018618
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of olopatadine hydrochloride eye drops for allergic conjunctivitis

Abstract: Background: Allergic conjunctivitis (AC) is a multifactorial and common type of ocular surface disease that affects many people. The quality of life for AC patients can be significantly decreased caused by symptoms of ocular itching, swelling, redness, and tearing. Topical antihistaminics, mast cell stabilizers, non-steroidal anti-inflammatory drugs (NSAIDs), and steroids have been widely used to treat AC. Many clinical trials have indicated that olopatadine hydrochloride eye drops can provide quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In a previous pharmacokinetic study, the concentrations of olopatadine were observed at the time points after single and multi-dose exposure in healthy subjects after 7d. Result showed that olopatadine was slowly absorbed in all participants and then rapidly eliminated from the body [20] . The common non-ocular adverse events associated with olopatadine include headache, nasal dryness, dysgeusia, and fatigue, which are known antihistamine effects [21][22] .…”
Section: Ketotifen and Olopatadine In The Treatment Of Allergic Conju...mentioning
confidence: 96%
“…In a previous pharmacokinetic study, the concentrations of olopatadine were observed at the time points after single and multi-dose exposure in healthy subjects after 7d. Result showed that olopatadine was slowly absorbed in all participants and then rapidly eliminated from the body [20] . The common non-ocular adverse events associated with olopatadine include headache, nasal dryness, dysgeusia, and fatigue, which are known antihistamine effects [21][22] .…”
Section: Ketotifen and Olopatadine In The Treatment Of Allergic Conju...mentioning
confidence: 96%
“…It belongs to a group of drugs called antihistamines, which act by impairing the impacts of histamine, a biomolecule in the body that causes allergic symptoms [18,19]. This drug comes in the form of eye drops and is commonly prescribed to relieve symptoms such as itching, redness, and watering of the eyes caused by allergies like hay fever or allergic conjunctivitis [20][21][22]. Most of the detection approaches for OLP are chromatographic approaches [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…However, these therapies are largely based on symptomatic relief. Besides, the duration of eye drops remaining active in the conjunctival sac is relatively short, and it is difficult to maintain their efficacy (10). When the hypersensitivity reaction is re-ignited, patient relapse can easily occur.…”
Section: Introductionmentioning
confidence: 99%